Short-term interest rate and own rate of money in Malaysian money demand function - Habibullah, Muzafar Shah (Penerbit Universiti Kebangsaan Malaysia, 1989)
This article has examined empirically the issues of the role of short-term interest rate and rate of return on money in a money demand function of a developing economy-Malaysia. The results suggest that short-term interest rate and rate of return on money play important role in the Malaysian money demand function, and excluding it from the model could subject it to misspecification error. Also, the model that incorporates short-term interest rate and the rate of return on money is stable over time (in Malaysia, this is true for M2). The results of ex-post forcast suggest that the model that incorporates both short-term interest rate and rate of return on money has better forecasting ability.